The use of virtual reality in the treatment of mental disorders such as phobias and post-traumatic stress disorder - Liana Spytska (Elsevier, 2024)
Mental disorders, such as phobias and post-traumatic stress disorder (PTSD), are a serious health problem that significantly impacts people's quality of life. These disorders can significantly impair the quality of life of patients, so studying ways to treat them using modern methods is important and relevant. The purpose of this study is to evaluate the effectiveness and potential of using virtual reality (VR) technology in the treatment of phobias and PTSD. The methods used in the study include analytical, comparative, and systematization methods. The study has shown that cognitive behavioural therapy and exposure therapy are the main treatments for these disorders. The use of VR in the treatment of mental disorders, including phobias and PTSD, opens up new opportunities for safe and effective exposure to stressful stimuli. It was found that the benefits of using VR in the treatment of mental disorders include safe exposure, an individualized approach to treatment, and the ability to create realistic simulations of stressful situations. The study confirmed that the use of VR in the treatment of phobias allows patients to gradually get used to phobic stimuli and change their negative perceptions and reactions to them. The use of VR in the treatment of PTSD has significant potential, allowing the application of various techniques, including exposure, gradual desensitization, cognitive behavioural therapy, therapeutic recovery, meditation, and relaxation, to alleviate the symptoms of the disorder and improve the quality of life of patients. The findings of the study can serve as a basis for improving clinical practice in psychotherapy and psychiatry, allowing for more effective and individualized care for patients with disorders.